2020
DOI: 10.3390/nu12030666
|View full text |Cite
|
Sign up to set email alerts
|

Body Dissatisfaction, Restrictive, and Bulimic Behaviours among Young Women: A Polish–Japanese Comparison

Abstract: The growing number of women, who are characterized by restrictive and bulimic behaviours towards their own body is observed especially in countries influenced by Westernalization. However, there is a lack of cross-cultural studies in this area. The main aim of the present study was to examine the psychological and socio-cultural risk factors for eating disorders in Polish and Japanese women. A cross-sectional research study was conducted among 18-to 29-year old Polish (n = 89) and Japanese (n = 97) women. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 76 publications
(114 reference statements)
3
35
0
3
Order By: Relevance
“…There were also no differences between Polish and Vietnamese women in terms of the intensification of restrictive behaviors and the pursuit of thinness. These results have been confirmed by other studies describing the importance of body dissatisfaction for the development of typical behaviors in eating disorders, such as in the Swedish studies by Forsén Mantilla and Birgegard [74], the Polish studies by Izydorczyk et al [32,75], and the Brazilian studies by de Carvalho, Alvarenga and Ferreira [49]. On the other hand, Rodgers and Melioli [51], in a review of 67 studies (emphasizing the important role of social media (i.e., the internet) and not taking into account psychological factors in these studies), indicated a significant relationship between the body image and behaviors related to the development of eating disorders in many countries in Europe, America, Australia, and Asia.…”
Section: The Characteristics Of Psychological Factors As Well As Restsupporting
confidence: 82%
See 1 more Smart Citation
“…There were also no differences between Polish and Vietnamese women in terms of the intensification of restrictive behaviors and the pursuit of thinness. These results have been confirmed by other studies describing the importance of body dissatisfaction for the development of typical behaviors in eating disorders, such as in the Swedish studies by Forsén Mantilla and Birgegard [74], the Polish studies by Izydorczyk et al [32,75], and the Brazilian studies by de Carvalho, Alvarenga and Ferreira [49]. On the other hand, Rodgers and Melioli [51], in a review of 67 studies (emphasizing the important role of social media (i.e., the internet) and not taking into account psychological factors in these studies), indicated a significant relationship between the body image and behaviors related to the development of eating disorders in many countries in Europe, America, Australia, and Asia.…”
Section: The Characteristics Of Psychological Factors As Well As Restsupporting
confidence: 82%
“…Saleh et al [76] did not compare Palestinian women with women of other nationalities, and age was significantly and negatively correlated with the results of the EAT-26 test in terms of describing restrictive and bulimic eating behaviors. As indicated by Izydorczyk et al [32], in studies conducted on Polish and Japanese women, the latter (similarly to the Vietnamese women in the research by Izydorczyk and the team presented in this article) showed a higher level of compulsive and bulimic behaviors than Polish women. Moreover, the Vietnamese women showed a similar level of striving for thinness and related restrictive behaviors as Polish and Japanese women, as well as a similar maturity fears [32].…”
Section: The Characteristics Of Psychological Factors As Well As Restsupporting
confidence: 73%
“…A literature review confirms the significance of the sociocultural impact of standards of body image promoted by mass media on the development of unhealthy eating behavior in different cultures (39). It is worth mentioning that the multifaceted influence of restrictive and buliming behaviors should be tested.…”
Section: Introductionmentioning
confidence: 79%
“…A fairly coherent picture has emerged from the analysis of the results of socio-cultural research in various cultures indicating the importance of, above all, the standards of one's own body image, shaped by mass media. The internalization of the value of having a slim body and dissatisfaction with one's own body as well as socio-cultural pressure associated with the pursuit of an ideal appearance have been indicated as key to the emergence of food restrictions [236][237][238].…”
Section: Psychopathologymentioning
confidence: 99%